MOF-Derived CoSe2@NiFeOOH Arrays for Efficient Oxygen Evolution Reaction - Yulong Tang; Jiangning Li; Zhiyi Lu; Yunan Wang; Kai Tao; Yichao Lin (Nanomaterials, 2023)
Water electrolysis is a compelling method for the production of environmentally friendly hydrogen, minimizing carbon emissions. The electrolysis of water heavily relies on an effective and steady oxygen evolution reaction (OER) taking place at the anode. Herein, we introduce a highly promising catalyst for OER called CoSe2@NiFeOOH arrays, which are supported on nickel foam. This catalyst, referred to as CoSe2@NiFeOOH/NF, is fabricated through a two-step process involving the selenidation of a Co-based porous metal organic framework and subsequent electrochemical deposition on nickel foam. The CoSe2@NiFeOOH/NF catalyst demonstrates outstanding activity for the OER in an alkaline electrolyte. It exhibits a low overpotential (η) of 254 mV at 100 mA cm−2, a small Tafel slope of 73 mV dec−1, and excellent high stability. The good performance of CoSe2@NiFeOOH/NF can be attributed to the combination of the high conductivity of the inner layer and the synergistic effect between CoSe2 and NiFeOOH. This study offers an effective method for the fabrication of highly efficient catalysts for an OER.